Computational Methods to Study the Structure and Dynamics of Biomolecules and Biomolecular Processes From Bioinformatics to Molecular Quantum Mechanics - Liwo, Adam.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book provides a comprehensive overview of modern computer-based techniques for analyzing the structure, properties and dynamics of biomolecules and biomolecular processes. It is organized in four main parts; the first one deals with methodology of molecular simulations; the second one with applications of molecular simulations; the third one introduces bioinformatics methods and the use of experimental information in molecular simulations; the last part reports on selected applications of molecular quantum mechanics. This second edition has been thoroughly revised and updated to include the latest progresses made in the respective field of research.
Molecular simulations: methodology -- Molecular simulations: applications -- Use of structural database or experimental information in modeling protein structure and dynamics -- Applications of molecular quantum mechanics.
Keywords: Computational intelligence; Bioinformatics; Proteins .; Chemistry, Physical and theoretical; Mathematical physics; Computational Intelligence; Computational and Systems Biology; Protein Biochemistry; Theoretical Chemistry; Theoretical, Mathematical and Computational Physics